The break between Lithuanian prehistory and history: a problematical analysis - Albinas Kuncevičius; Aleksiejus Luchtanas (Lietuvos Istorijos Studijos)
• In the broad sense, prehistory and history are two major and complementary components of a unified approach to historical research.